2019
DOI: 10.11591/ijpeds.v10.i1.pp160-169
|View full text |Cite
|
Sign up to set email alerts
|

Smart database concept for Power Management in an electrical vehicle

Abstract: <p>As world population continues to grow and the limited amount of fossil fuels begin to diminish, it may not be possible to afford the needed amount of energy demanded by the world by only using fossil fuels. Meanwhile, the abundant nature of renewable energy sources brings new beginning for next generations. Greater penetration of electric vehicles will play an important role in building green and healthy world. The main remaining issue to make the switch from conventional to electric vehicle is perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…By processing such information EVs can be classified and buildings can make recommendations according to their positions. Another smart database for power management EVs by the same authors can be found in [29].…”
Section: Related Workmentioning
confidence: 99%
“…By processing such information EVs can be classified and buildings can make recommendations according to their positions. Another smart database for power management EVs by the same authors can be found in [29].…”
Section: Related Workmentioning
confidence: 99%
“…IoT and cloud computing can be used to develop an efficient communication system [34]. Increased penetration of electric vehicles in the conventional system has given rise to the need of optimal voltage control of the distribution system and efficient power management of an electric vehicle [35], [36]. However, the approach towards developing a load management system based on regional classification of loads is yet to be taken.…”
Section: Introductionmentioning
confidence: 99%
“…This fundamental experimentation helps to understand the behavior of battery during vehicle deceleration. The communication and car learing based novel power management architecture is introduced in [9]. This architecture is based on smart data base concept.…”
Section: Introductionmentioning
confidence: 99%